Composição e distribuição espacial e temporal de larvas de Chironomidae (Insecta, Diptera), em um rio em região montanhosa, no extremo sul do Brasil - Floss, Elzira Cecilia Serafini (2011)
The composition and spatio-temporal distribution of the taxocenoses of the larvae of Chironomidae of a mountainous river, in southernmost Brazil were analyzed for this study. The diversity found was also compared to the taxocenoses of larvae inventoried in other Brazilian regions by means of tests of hypotheses, based on some environmental factors on a regional scale. About 100 taxa, classified at genus or species level, were found in the middle course of the Rio Jacuí basin (in the State of Rio Grande do Sul). The specimen collection took place in twelve different places between April 2000 and May 2002. The dominant taxa belong to species of the genera Rheotanytarsus, Cricotopus, Polypedilum and Pseudochironomus. Around 22% of the taxa were rare and 15 genera (Aedokritus, Axarus, Endotribelos, Kiefferulus, Manoa, Oukuriella, Phaenopsectra, Stenochironomus, Xenochironomus, Xestochironomus, Onconeura, Cardiocladius, Metriocnemus, Paracladius and Rheocricotopus) are new occurrences to Rio Grande do Sul. The clustering analysis applied to the genera, using larvae‟s taxocenoses inventoried in 32 regions of Brazil, formed three groups that showed similarity higher than 50%. The groups, when discarded the effects of spatial autocorrelation, displayed weak and positive correlation between the taxocenosis composition and the type of aquatic system and drainage basin and weak and negative in relation to the biome. The spatial and temporal structure of the taxocenoses, analyzed after four seasonal samplings (winter, spring, summer and autumn) in four different sampling locations showed that dominance, just like abundance and richness, varied amongst the different spots and seasons studied. Variations in spatial distribution were influenced by the existence of marginal vegetation, substratum heterogeneity, gradient of preservation and altitude. Variations in temporal distribution were influenced by factors such as mean temperature and precipitation levels, which were also related to the distribution of certain taxa and to the structure of the taxocenoses. The significant richness of the surveyed region corroborates some tendencies already noticed in other parts of the world, such as: i) lotic systems may constitute an exception to the rule that states that diversity is greater in tropical regions; ii) terrain transition regions may contain the greatest richness of Chironomidae; and iii) the spatial distribution of Chironomidae may be influenced in the greater extent due to local environmental characteristics than regional ones. On the other hand, human activity such as deforestation and construction of dams constitutes a serious threat to the conservation of the taxocenoses of Chironomidae since they directly affect the conservation of the riparian vegetation and the heterogeneity of the habitat.